2018
DOI: 10.5114/hivar.2018.73337
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of hepatitis B and C virus infection among HIV- and non-HIV-infected patients in Benin City, Nigeria

Abstract: Introduction: Seasonal variation in immunity has been found in healthy individuals and in association with some diseases. Data on seasonal prevalence of hepatitis B virus (HBV) and hepatitis C virus (HCV) infection is sparse. This study aimed at determining the seasonal seroprevalence of HBV and HCV infections among human immunodeficiency virus (HIV)-infected patients in Benin City.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 15 publications
5
3
0
Order By: Relevance
“…Pregnant women are at increased risk of UTI but in many cases uropathogenic bacterial infections remain asymptomatic [1,4,8,10,12,18,21,[33][34]. In this research, the overall prevalence of ASB uropathogens among pregnant women was 29.1%, which is in harmony with the documented research from Iranian population [35], which reported the same prevalence of 29.1%.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Pregnant women are at increased risk of UTI but in many cases uropathogenic bacterial infections remain asymptomatic [1,4,8,10,12,18,21,[33][34]. In this research, the overall prevalence of ASB uropathogens among pregnant women was 29.1%, which is in harmony with the documented research from Iranian population [35], which reported the same prevalence of 29.1%.…”
Section: Discussionsupporting
confidence: 86%
“…Highest prevalence of ASB uropathogens was observed in the age range of 26-31 years for both pregnant and nonpregnant women and the mean ages of 23.3±5.2 and 24.2±5.6 years were stipulated for pregnant and non-pregnant women respectively in this study, which was similar to that reported in Hawassa referral hospital [12], Ambo town [16] Gondar tertiary teaching hospital [6] in Ethiopian cities, Benin city [1,39], Ibadan [33] and University of Uyo teaching hospital, Nigeria [4]. The increased prevalence observed within this age range may be attributed to multiparity which has been documented as one of the risk factors for ASB in pregnant women in many populations [4,[15][16][17]44).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations